Phase I trial of capecitabine and weekly irinotecan in combination with radiotherapy for neoadjuvant therapy of rectal cancer - Hofheinz, Ralf-Dieter; Gerstenbergk-Helldorf von Zech, Bolko von; Wenz, Frederik; Gnad, Ulrike; Kraus-Tiefenbacher, Uta; Müldner, Albrecht; Hehlmann, Rüdiger; Post, Stefan; Hochhaus, Andreas; Willeke, Frank (Journal of clinical oncology, 2005)
Purpose To establish the feasibility and efficacy of capecitabine in combination with weekly irinotecan (CAPIR) with concurrent pelvic radiotherapy (RT) in patients with locally advanced rectal cancer. Patients and Methods Nineteen patients with rectal cancer clinical stage T3-4, Nx received weekly irinotecan 50 m/m(2) (days 1, 8, 15, 22, 29) and two doses of capecitabine (days 1 through 38; dose level [DL] I, 500 mg/m(2) bid, DL II, 625 mg/m(2) bid) according to phase I methodology. Three-dimensional conformal RT was given to a dose of 50.4 Gy (45 Gy + 5.4 Gy). Results On DL I, no dose-limiting toxicities occurred, whereas diarrhea grade 3 affected three of seven patients on DL II. Twelve patients were treated on DL I and received a median relative dose-intensity of 100% for both drugs. Grade 3 or 4 adverse events were observed in only one of these patients (asthenia grade 3). All patients underwent surgery and R0 resection was achieved in all patients. Pathologic complete remission was observed in four patients and another five patients had only microfoci of residual tumor. Conclusion Preoperative chemoradiotherapy with CAPIRI is feasible and well tolerated. The preliminary efficacy is good, and the tolerability is at least comparable with data for fluorouracil plus irinotecan chemoradiotherapy. Larger phase II trials of the CAPIRI-RT schedule clearly are warranted.